Pengaruh Live Selling, Content Marketing dan Influencer terhadap Keputusan Pembelian Produk Lozy Hijab di E-Commerce - Puspitasari, Natasya Dwi; Hariasih, Misti; Indayani, Lilik (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This digital era has caused a paradigm shift in society who in their daily lives have done all their activities by utilizing the internet. This also has an impact on the process of reforming the Muslim fashion model in Indonesia. One of the fashion brands oriented in the modern era is Lozy Hijab. This study aims to analyze the effect of Live Selling, Content Marketing, and Influencers on purchasing decisions for Lozy Hijab products in E-Commerce. This research was conducted using quantitative methods with the population being people who are active users of social media and consumers of Lozy Hijab products. Sampling was carried out using non-probability sampling techniques through the quota sampling method so that a sample of 96 respondents was obtained. Data analysis in this study was carried out using the SPSS version 25 tool. So that the results obtained state that Live Selling, Content Marketing, and Influencers have an effect on purchasing decisions for Lozy Hijab products in E-Commerce.